2006
DOI: 10.1038/sj.eye.6702527
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional outcome of surgery of primary rhegmatogenous retinal detachment in high myopic eyes

Abstract: Purpose To analyse the anatomical and functional outcome of surgery for primary rhegmatogenous retinal detachment (RRD) in highly myopic eyes. Methods We retrospectively reviewed the medical records of 111 high myopic patients (111 eyes) with primary RRD treated by scleral buckling or pars plana vitrectomy in a tertiary referral university hospital. The postoperative retinal status and best-corrected visual acuity were recorded. Risk factors including age, refractive error, duration of retinal detachment, preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…The ages of the subjects should especially be considered. The average age was 33.2–35.9 in the studies among patients with high myopia,51–53 which was younger than 38.9–61.3 in the studies among patients with RRD including non-high myopia and high myopia 8,16,41,55,56. It suggests that SB was performed in younger age in high myopic patients.…”
Section: Introductionmentioning
confidence: 85%
“…The ages of the subjects should especially be considered. The average age was 33.2–35.9 in the studies among patients with high myopia,51–53 which was younger than 38.9–61.3 in the studies among patients with RRD including non-high myopia and high myopia 8,16,41,55,56. It suggests that SB was performed in younger age in high myopic patients.…”
Section: Introductionmentioning
confidence: 85%
“…The final reattachment rate was 97.2% for the SB group and 100% for the PPV group. Cheng et al [9] reported the anatomical success rate in the amount of 86.5% after the primary vitreoretinal surgery and the final anatomical success rate was 100%. Bernheim et al [10] showed in their prospective study the final reattachment rate referring to the high myopia in the amount of 96%.…”
Section: Discussionmentioning
confidence: 99%
“…Kwok et al [8] reported that 62.5% of the eyes undergoing the primary pars plana vitrectomy reached the visual acuity of 20/60 or better. Cheng et al [9] demonstrated that 26.3% of eyes achieved the postoperative vision 20/50 or better in the pars plana group and 68.5% of the eyes in the scleral buckling group. The obvious difference in functional result between both groups could be explained by the fact that the vitrectomy was used only in more complicated RD cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the very long axial length and the generalized thinning of the sclera, muscle avulsion, vortex vein damage, hemorrhage, retention of subretinal fluid after internal drainage, and risk of globe perforation have been noted during surgery in highly myopic eyes [5, 6]. …”
Section: Introductionmentioning
confidence: 99%